2015
DOI: 10.3329/ralf.v1i1.22370
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaplasmosis in cattle in Sirajganj district of Bangladesh

Abstract: An epidemiological investigation was conducted to ascertain the prevalence of anaplasmosis in cattle in Sirajganj district of Bangladesh, during the period of December 2013 to November 2014. During one year study period a total of 395 cattle were examined, and where 102 were found to be infected with Anaplasma spp. On Geimsa stained blood smear examination, it was observed that the overall prevalence of anaplasmosis in cattle was recorded as 25.82%. The effect of area, age, sex, breed and season was observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
6
9
0
Order By: Relevance
“…Anaplasma marginale was the fourth most prevalent TBP detected in this study. The prevalence of A. marginale recorded here is consistent with the previous findings reported from different region of the country (Alim et al., ; Belal et al., ; Chowdhury et al., ; Rahman et al., ). A. marginale has a worldwide distribution and is considered to be the most prevalent TBPs causing high morbidity and mortality of cattle in subtropical and tropical countries (Kocan, de la Fuente, Blouin, Coetzee, & Ewing, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Anaplasma marginale was the fourth most prevalent TBP detected in this study. The prevalence of A. marginale recorded here is consistent with the previous findings reported from different region of the country (Alim et al., ; Belal et al., ; Chowdhury et al., ; Rahman et al., ). A. marginale has a worldwide distribution and is considered to be the most prevalent TBPs causing high morbidity and mortality of cattle in subtropical and tropical countries (Kocan, de la Fuente, Blouin, Coetzee, & Ewing, ).…”
Section: Discussionsupporting
confidence: 93%
“…Microscopic examination of Giemsa‐stained thin blood smears revealed that eighteen slides were positive (4.7%, 18/384) for Anaplasma spp., supporting previous reports in Bangladesh (Alim et al., ; Belal et al., ; Chowdhury et al., ). None of the smears was found to be positive for Babesia and Theileria species, which can be explained by the low sensitivity of this technique in combination with typically low parasitemia in healthy carrier animals (Salih, El Hussein, Seitzer, & Ahmed, ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Even though statistically not significant, there was more anaplasma infection found in female (16.19%) than the male goats (15.23%) which was consistent with Yousefi et al (2017) in goats and Belal et al (2014) in cattle. They reported that females were more susceptible to anaplasmosis because of stress and insufficient supply of feed during high demand in pregnancy (Kamani et al, 2010).…”
Section: Discussionsupporting
confidence: 54%